2010
DOI: 10.1038/ki.2009.382
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrical dimethylarginine is associated with renal and cardiovascular outcomes and all-cause mortality in renal transplant recipients

Abstract: Increased plasma levels of asymmetric dimethylarginine (ADMA) are associated with endothelial dysfunction and predict the progression to dialysis and death in patients with chronic kidney disease. The effects of these increased ADMA levels in renal transplant recipients, however, are unknown. We used the data from ALERT, a randomized, double-blind, placebo-controlled study of the effect of fluvastatin on cardiovascular and renal outcomes in 2102 renal transplant recipients with stable graft function on enrollm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
1
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 45 publications
1
45
1
4
Order By: Relevance
“…In contrast to many studies [1,11,[32][33][34][35], the outcomes of the current study show that in the relapse phase, ADMA was negatively correlated with cholesterolemia and triglyceridemia. There are several explanations for these controversial results.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…In contrast to many studies [1,11,[32][33][34][35], the outcomes of the current study show that in the relapse phase, ADMA was negatively correlated with cholesterolemia and triglyceridemia. There are several explanations for these controversial results.…”
Section: Discussioncontrasting
confidence: 52%
“…Another significant cause of presumed high ADMA concentrations in these children is endothelial dysfunction due to biochemical disturbances and hypertension, which is commonly found. In children with NS, cardiovascular events, including myocardial infarction, may result from early atherosclerosis due to endothelial dysfunction [31,32]. The aim of this study was to ascertain whether ADMA may play a role as an early marker for atherosclerosis in children with NS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it might influence NO and GFR levels and affect atherosclerosis formation. Several studies suggested that ADMA level can be an independent risk factor for progression of CKD (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Elevated ADMA reduces bioavailability of NO and induces endothelial dysfunction and may be involved in the pathophysiology of cardiovascular disease in CKD (8).…”
Section: Discussionmentioning
confidence: 99%
“…[12] With respect to SDMA, initial studies did not find an association with adverse outcomes, [7,13,14] but some more recent studies reported positive associations with all-cause mortality or CVD. [11,15,16] Overall, prior studies on ADMA/SDMA and CVD or all-cause mortality were derived from many different study populations (general population, [15,17,18] patients with CVD, [9,11,19,20] renal diseases, [7,13,[21][22][23][24] diabetes, [25,26] or critically ill patients from intensive care unit,[27-29] respectively), differed in their methodological approaches (e.g. using types of samples (plasma vs. serum) or methods to determine the biomarker levels (HPLC vs. tandem mass spectroscopy vs. ELISA), or considered different confounders in their analysis.…”
Section: Introductionmentioning
confidence: 99%